A Design of a High-Voltage On-board Battery Charger for Electric Vehicles - Lê Thanh Phúc; Huỳnh Quốc Việt (Journal of Technical Education Science, 2025)
This paper presents results on the design of an on-board battery charger (OBC) for electric vehicles. The role of the charger is to convert AC to DC power, then supply it to the high-voltage battery pack. The state space averaging method is used to model the DC/DC converter. The converter is operated at the discontinuous conduction mode (DCM). This model is used as part of the design of an OBC with high voltage feedback. The OBC model can maintain high voltages in accordance with the requirements of today’s battery packs in electric vehicles. The selected 100kHz is the operating frequency of the DC/DC converter. For the no-load test, the output voltage on the secondary winding after of rectification is maintained at 310V. The test results show that the electronic components work effectively under high voltage. The OBC model provides a continuous charging current to the battery pack used for testing motors in electric vehicles.